Corydalis mianxianensis (Papaveraceae), a new species from limestone cliffs in central China, and notes on the Shaanxi record of C. saxicola G.S.Bunting - Wang, Dong; Xu, Xiaodong; Li, Niya; Sun, Qian; Wang, Liang (Phytotaxa, 2023)
Corydalis mianxianensis, a new species of C. sect. Cheilanthifoliae Lidén (Papaveracae), is described from Qinling-Daba mountains and adjacent Minshan mountains, central China. It is similar to C. moupinensis Franch., but it differs from the latter in racemes with 30–50(–70) flowers, spur being much shorter than limb of upper petal, and arcuate to strongly contorted fruits. These two species are also much different in stigma and ecology as well. In addition, we confirmed that the record of C. saxicola G.S.Bunting in Shaanxi Province as documented in the Chinese floras was a misidentification of this new species.